Productivity Analysis of Crude Palm Oil (CPO) in PT. Ramajaya Pramukti Using Value Stream Mapping Approach - Dhimas Budhi Pratama; Anita Susilawati (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
This study aims to analyze the productivity of CPO processing using Value Stream Mapping (VSM) approach. A case study conducted in PT. Ramajaya Pramukti, Indonesia. The research method used the VSM and Process Activity Mapping (PAM) to determine wastes in the process flow of CPO production. The data was collected in 1 month. The preliminary result of CPO productivity process was average of 73.67%. Based the Future Value Stream Mapping (FVSM) the CPO processing time can be efficient from 1.981 seconds/kg to 1.963 seconds/kg. The productivity processing for value added 1.525 seconds/kg, which non value added of 0.012 and the non necessary value added of 0.383 seconds/kg. The quality of raw materials was the biggest waste contributor. It was caused a longer processing time due to poor quality of raw materials.